The Paston Treasure microcosm of the known world - Moore, Andrew 1952-; Flis, Nathan 1982-; Vanke, Francesca (Yale Center for British Art, 2018)
The Paston Treasure, a spectacular painting from the 1660s now held at Norwich Castle Museum, depicts a wealth of objects from the collection of a local landed family. This deeply researched volume uses the painting as a portal to the history of the collection, exploring the objects, their context, and the wider world they occupied. Drawing on an impressive range of fields, including history of art and collections, technical art history, musicology, history of science, and the social and cultural history of the 17th century, the book weaves together narratives of the family and their possessions, as well as the institutions that eventually acquired them. Essays, vignettes, and catalogue entries comprise this multidisciplinary exposition, uniting objects depicted in the painting for the first time in nearly 300 years. Exhibition: Yale Center for British Art, New Haven, USA (15.02-27.05.2018); Norwich Castle Museum & Art Gallery, UK (23.06-23.09.2018)
Titel der Ausstellungen: "The Paston Treasure: Microcosm of the known world" (Yale Center of British Art, New Haven, 15.02.2018-27.05.2018) und "The Paston Treasure: riches and rarities of the known world" (Norwich Castle Museum & Art Gallery, 23.06.2018-23.09.2018)
Keywords: Paston -- Familie; Geschichte 1600-1900; Naturkundliche Sammlung; Raritätenkammer; Sammlung; Gemälde; Kunst; Ausstellungskatalog -- Yale Center for British Art -- 15.02.2018-27.05.2018 -- New Haven, Conn.; Ausstellungskatalog -- Norwich Castle Museum & Art Gallery -- 23.06.2018-23.09.2018 -- Norwich; Bildband